القيم الإخبارية في القنوات الفضائية الجزائرية دراسة تحليلية مقارنة في المضمون والقائم بالإتصال في قنوات الجزائرية الثالثة، دزاير تيفي و قناة الخبر - بن عودة موسى (My University, 2018)
In our study, we discuss the subject of news values under the heading of news values in the Algerian satellite channels( ALGERIE 3, DZAIR TV AND ELKHABAR CHANNEL) where we conducted a comparative analysis of the main news bulletins in the Algerian satellite channels this is in order to know its form, content, and the most important news values it contains. This is by adopting the methods of scientific research using the content analysis technique, as we deal in our study of communication in these channels through the recognition of its general characteristics and its rehabilitation characteristics and social conditions and pressures that may be exposed in and Outside his organization and his view of the concept of values and its role in the process of collecting news and editing and dealing with various sources of news during the exercise of his field work and we have distributed investments to them to know all thisThe most prominent findings of the study and the existence of similarity in the matrix of news values in the third Algerian public channel EL-KHABAR AND DZAIR TV CHANNELS, with a slight difference in the order of these values and these channels focus on the news close to the citizen and rely on various sources in the coverage of news in return we have the effect of a number of pressures Internal and external on the contact list the most important pressure news sources and the editorial policy of the channel and is wl2hat it faces in the coverage of the news as we have reached the awareness of the contact with the subject of values of news, but its role is limited in the selection and arrangement.